2018
DOI: 10.3389/fncel.2018.00095
|View full text |Cite
|
Sign up to set email alerts
|

IL-33/ST2L Signaling Provides Neuroprotection Through Inhibiting Autophagy, Endoplasmic Reticulum Stress, and Apoptosis in a Mouse Model of Traumatic Brain Injury

Abstract: Interleukin-33 (IL-33) is a member of the interleukin-1 (IL-1) cytokine family and an extracellular ligand for the orphan IL-1 receptor ST2. Accumulated evidence shows that the IL-33/ST2 axis plays a crucial role in the pathogenesis of central nervous system (CNS) diseases and injury, including traumatic brain injury (TBI). However, the roles and molecular mechanisms of the IL-33/ST2 axis after TBI remain poorly understood. In this study, we investigated the role of IL-33/ST2 signaling in mouse TBI-induced bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 58 publications
(89 reference statements)
6
36
0
Order By: Relevance
“…In this study, we demonstrated an unreported role of IL‐33 in counteracting DCM by inhibiting ER stress‐related cardiomyocyte apoptosis. In fact, IL‐33 has been reported to modulate ER stress in other cells (Gao et al, 2018; Hasnain et al, 2014), suggesting that IL‐33 is an important regulator of ER stress. However, the precise mechanism by which IL‐33 modulates ER stress is not described in these studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we demonstrated an unreported role of IL‐33 in counteracting DCM by inhibiting ER stress‐related cardiomyocyte apoptosis. In fact, IL‐33 has been reported to modulate ER stress in other cells (Gao et al, 2018; Hasnain et al, 2014), suggesting that IL‐33 is an important regulator of ER stress. However, the precise mechanism by which IL‐33 modulates ER stress is not described in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study demonstrated that it inhibited the FFA uptake receptor, CD36, in macrophages (Zhang et al, 2017). In the fields out of the cardiovascular system, IL‐33 is found to be implicated in the regulation of autophagy and ER stress (Dickinson et al, 2016; Gao et al, 2017, 2018; Wu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Serum sST2 levels are also elevated in TBI patients, and the increased concentrations are positively related to inflammation, severity and prognosis (55), which indicates that sST2 is a potential prognostic biomarker for TBI. In mice, IL-33 is released immediately from damaged oligodendrocytes and astrocytes in injured CNS tissue during TBI induced by controlled cortical impact (CCI) and experimental SCI (4,11,13,56).…”
Section: Il-33 In Traumamentioning
confidence: 99%
“…IL-33 is released from apoptotic and necrotic cells as a vigilant signaling molecule ( Palmer et al, 2009 ), and its synthesis, localization, and secretion are closely related to its dual functional properties. Indeed, IL-33 plays a double-edged sword in a variety of diseases, such as intracerebral hemorrhage (ICH) ( Gao et al, 2017b ), traumatic brain injury (TBI) ( Gao et al, 2018 ) and central multiple sclerosis (MS) ( Jafarzadeh et al, 2016 ). On the one hand, exogenous IL-33 can inhibit autophagic cell death and inflammatory responses, thereby protecting neurons from damage ( Gao et al, 2017b ).…”
Section: Introductionmentioning
confidence: 99%